Design and develop a one DOF wrist robot for mobilization of PS human joints - Monteiro Ephraim Keith. (2012)
Wrist robots are important in the areas of wrist rehabilitation and haptic feedback purposes and there exists a need to improve the mechanics and ergonomics of existing wrist devices. The project focuses on actuation on 1 of the 3 degree of freedoms (DOF) of a wrist movement which is the pronation-supination (PS) movement. There exist numerous wrist devices but they are generally heavy and portray high perturbation to the user’s wrist during operation. The author would seek to design and implement a wrist robot that has low weight and low perceived inertia by grounding the motors used for actuation as well as having the rotation of the robot in line with the axis of rotation of the PS joint. A flexible and lightweight capstan and drum system is also implemented for the actuation of PS wrist movements and perceived inertia results were compared with an existing wrist robot, the MIT Manus. The author’s wrist robot showed a perceived inertia value of 8.55E-4 kg.m² which has considerably lower perceived inertia values compared to 2.93E-3 kg.m² of the MIT Manus and this would mean less strain on the user’s wrist during usage. The wrist robot could be used in future designs of 3 Degree-of-Freedom wrist robots that require good ergonomics and minimal strain to the user’s wrist.